The Alaska Yukon Region of the Circumboreal Vegetation map (CBVM). - Jorgensen, T.; Meidlinger, D. (Conservation of Arctic Flora and Fauna (CAFF)., 2015)
"The circumboreal vegetation mapping (CBVM) project is an international collaboration among vegetation scientists to create a new vegetation map of the boreal region at a 1:7.5 million scale with a common legend and mapping protocol (Talbot and Meades 2011). The map is intended to portray potential natural vegetation, or the vegetation that would exist in the absence of human or natural disturbance, rather than existing vegetation that is commonly generated at larger scales. This report and map contributes to the CBVM effort by developing maps of bioclimatic zones, geographic sectors with similar floristic variability, and vegetation in boreal Alaska, Yukon, northwestern British Columbia, and a mountainous portion of southwest Northwest Territories—termed the Alaska-Yukon region. It further develops the mapping from the initial classification and proto-type mapping efforts for southwestern Alaska (Jorgenson 2012) and western Canada (Meidinger and MacKenzie 2012) to this broader area." /./